2018
DOI: 10.1002/jsfa.9292
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of starch from different bean genotypes and its effect on biodegradable films

Abstract: The morphological, mechanical and water vapor barrier properties of films elaborated with common bean starch vary greatly as a function of the bean genotype used for starch production. © 2018 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 33 publications
2
12
0
Order By: Relevance
“…The morphological aspect of the starch observed in Figure 5(A) is in accordance with the description of Agunbiade and Longe [29], which confirmed that grain lengths in all samples were mostly larger than their widths. With the enlargement of the starch grains of the same Figure 5(B), it is possible to perceive the presence of protrusions.…”
Section: Cowpeasupporting
confidence: 87%
“…The morphological aspect of the starch observed in Figure 5(A) is in accordance with the description of Agunbiade and Longe [29], which confirmed that grain lengths in all samples were mostly larger than their widths. With the enlargement of the starch grains of the same Figure 5(B), it is possible to perceive the presence of protrusions.…”
Section: Cowpeasupporting
confidence: 87%
“…However, BSM film crosslinked by SA showed the highest degree of crystallinity because of the lowest acidity and steric hindrance of SA. In spite of the decrease in degree of crystallinity of crosslinked BSM films, the degree of crystallinity was still higher than that of bio‐based films …”
Section: Resultsmentioning
confidence: 99%
“…Various avenues for starch modification have proven valuable for influencing the properties of resulting starch films. Work by Vanier et al (2019) showed that common bean starch of different genotypes, although grown in the same location and harvested at the same moisture content, would produce films with different properties. It was found that BRS Pitanga and BRS Pérola, for example, exhibited the highest TS, while BRS Estilo had the highest EAB and IPR Uirapuru had the smallest WVP (Table 2, entry 48).…”
Section: Starch Modificationmentioning
confidence: 99%
“…Such characteristics include amylose/amylopectin molecular weight, protein content, phosphate monoester content, granular morphology, granule size, and granule size distribution, all of which can vary depending on the starch source (granule size and distributions are highlighted in Figure 3). Even seemingly minute details, such as different cultivars of the same species or when in the plant's lifecycle the starch was extracted, can have consequential impacts on film properties (Baranzelli et al., 2019; Colussi et al., 2017; Dai et al., 2019; Domene‐Lopez et al., 2019; Pajak et al., 2019; Vanier et al., 2019).…”
Section: Hurdles To Developing Starch‐based Filmsmentioning
confidence: 99%